2020
DOI: 10.1002/gps.5450
|View full text |Cite
|
Sign up to set email alerts
|

Importance of loneliness in behavioral and psychological symptoms of dementia

Abstract: Objectives Loneliness is considered to be a crucial factor in mental health of elderly people. However, the effects of loneliness on behavioral and psychological symptoms of dementia (BPSD) have not been fully examined. The aim of this study was to investigate whether loneliness in patients with dementia is related to BPSD. Methods A total of 152 patients with dementia were assessed using the Neuropsychiatric Inventory (NPI‐12) and the revised University of California at Los Angeles (UCLA) loneliness scale. Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 29 publications
3
27
0
Order By: Relevance
“…Social isolation might cause the feeling of loneliness, which can exacerbate behavior alterations. These conclusions align with those found in a very recent work, which assessed the NPI and the revised University of California at Los Angeles (UCLA) loneliness scale [ 34 ]. The revised UCLA loneliness scale score was not significantly associated with age, education, Mini-Mental state examination score, gender, physical impairments and marital status.…”
Section: Discussionsupporting
confidence: 91%
“…Social isolation might cause the feeling of loneliness, which can exacerbate behavior alterations. These conclusions align with those found in a very recent work, which assessed the NPI and the revised University of California at Los Angeles (UCLA) loneliness scale [ 34 ]. The revised UCLA loneliness scale score was not significantly associated with age, education, Mini-Mental state examination score, gender, physical impairments and marital status.…”
Section: Discussionsupporting
confidence: 91%
“…Victor et al ( 39 ) found that 30.1% of 1,547 dementia patients reported feeling moderately lonely. Loneliness is also a risk factor for psychiatric behavioral problems in patients with dementia ( 40 ). Chinese scholars have also conducted studies on the psychological problems of dementia patients and their caregivers ( 41 , 42 ), but have not yet intervened using the Montessori approach.…”
Section: Discussionmentioning
confidence: 99%
“…Although longitudinal studies cannot establish causal directionality, these studies consistently demonstrate an association between loneliness and subsequent cognitive decline [ 63 ]. Loneliness has reliably been associated with increased risk of Alzheimer’s disease and related dementias [ 66 , 67 , 68 , 69 ], in addition to worse behavioral and psychological symptoms of dementia [ 70 ]. Moreover, this increase in dementia risk seems to be most relevant for individuals with persistent loneliness compared to individuals with transient loneliness in whom dementia risk remains unchanged [ 67 ].…”
Section: Discussionmentioning
confidence: 99%